Volatile Organic Compounds of Medicinal Values from Nepalese Acorus calamus L. - Gyawali, Rajendra; Kim, Kyong-Su (Kathmandu University Journal of Science, Engineering and Technology, 2009)
The volatile organic compounds (VOCs) from the rhizomes of Nepalese Acorus calamus L. were isolated using the simultaneous distillation–extraction (SDE) technique and subsequently analyzed via gas chromatography–mass spectrometry (GC-MS). A total of fifty-three VOCs were identified, belonging to various chemical classes including alcohol (11), aldehyde (14), ester (3), furan (1), hydrocarbon (19), ketone (4), N-containing, miscellaneous (1). The yield of volatile compounds obtained from the rhizomes of A. calamus was found to be 7493.59 mg/kg. Several bioactive compounds were identified, including β-asarone (46.78%), [E,Z]-2,4-decadienal (14.15%), linalool (0.41%), farnesol (11.09%), methyleugenol (6.10%), α- and β-pinene (both 0.06%), [E]-caryophyllene (0.11%), β-elemene (0.39%), ocimene (0.7%), aromadendrene (0.26%), and camphor (0.03%).